2002
DOI: 10.1159/000063912
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Rearrangement of the T Cell Receptor Gamma-Chain in Lichenoid Pigmented Purpuric Dermatitis of Gougerot-Blum Responding to Topical Corticosteroid Therapy

Abstract: Lichenoid pigmented purpuric dermatitis of Gougerot-Blum belongs to a group of closely related disorders which are termed pigmented purpuric dermatoses. It clinically manifests itself with grouped lichenoid papules in association with purpuric lesions. We report a case of lichenoid pigmented purpuric dermatitis of Gougerot-Blum with a heavy band-like CD4-positive lymphocytic infiltrate and clonal rearrangements of the γ-chain of the T cell receptors as detected by polymerase chain reaction/denaturing gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…There are several clinical subtypes in MF, i.e. granulomatous MF [2], hyperkeratotic MF [3], hypopigmented MF [4], MF associated with follicular mucinosis [5], MF bullosa [6], MF palmaris et plantaris [7, 8, 9], ichthyosiform MF [10], granulomatous slack skin [11], MF evolving from pityriasis lichenoides chronica [12], lichenoid pigmented purpuric dermatitis of Gougerot-Blum [13]and pagetoid reticulosis [14]. Recently, in relation to MF, a distinct clinicopathological variant, pilotropic lymphoma, has been described [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…There are several clinical subtypes in MF, i.e. granulomatous MF [2], hyperkeratotic MF [3], hypopigmented MF [4], MF associated with follicular mucinosis [5], MF bullosa [6], MF palmaris et plantaris [7, 8, 9], ichthyosiform MF [10], granulomatous slack skin [11], MF evolving from pityriasis lichenoides chronica [12], lichenoid pigmented purpuric dermatitis of Gougerot-Blum [13]and pagetoid reticulosis [14]. Recently, in relation to MF, a distinct clinicopathological variant, pilotropic lymphoma, has been described [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…19,21 Earlier studies have demonstrated clonality in PPD. [7][8][9]13 Almost 50% of the cases in our study showed a monoclonal or oligoclonal pattern. From a molecular perspective, the demonstration of an identical T-cell clone at multiple sites over time in several of our patients is corroborative evidence that this process is a clonally driven one without a discernible antigenic trigger.…”
Section: Discussionmentioning
confidence: 50%
“…7 There is an emerging body of clinical, phenotypic, and molecular data suggesting that PPD may represent an insidious epitheliotropic T-cell dyscrasia. [7][8][9][10][11][12][13][14][15] Although progression to mycosis fungoides (MF) is described, the literature precedent in this regard is limited, with only 11 reported cases. 9,11,12,[14][15][16] However, it is possible that underreporting accounts for the few patients described in the literature.…”
mentioning
confidence: 99%
“…Thus, it is not possible to know if histological signs of MF were present from the beginning. However, histology, immunohistochemistry and TCR gene analysis are not always sufficient to distinguish PPD from early MF [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the 1990s, MMF has been used as an immunosuppressive agent to prevent acute rejection after organ transplantation [2]. MMF has also been used alone or in combination with corticosteroids in autoimmune blistering diseases such as bullous pemphigoid [3][4][5], pemphigus vulgaris [4][5][6] and pemphigus foliaceus [4,7]. Recently, 2 reports on the therapeutic effect of MMF in epidermolysis bullosa acquisita (EBA) have been published with conflicting results [8,9].…”
Section: Discussionmentioning
confidence: 99%